Experimental and theoretical studies on gold(iii) carbonyl complexes: reductive C, H- and C, C bond formation. Issue 25 (3rd June 2021) - Ahrens, Alexander; Lustosa, Danilo M.; Karger, Leonhard F. P.; Hoffmann, Marvin; Rudolph, Matthias; Dreuw, Andreas; Hashmi, A. Stephen K.
Abstract : Transient cationic (C^C)gold(iii ) carbonyls act as electrophiles, leading either to reductive C, H bond formation via a water-gas-shift-type reaction or a reductive C, C bond formation via a gold(iii ) carboxylate. Abstract : The reactivity of cationic (C^C)gold(iii ) carbonyl complexes was investigated. While the in situ -formed IPrAu(bph)CO + complex (bph = biphenyl-2, 2′-diyl) does not undergo a migratory insertion of CO into the neighboring gold–carbon bond, nucleophiles can attack the coordinated CO moiety intermolecularly. Water as a nucleophile initiates a CO2 extrusion combined with a reductive C, H bond formation. The rapid formation of a gold(i ) species from an intermediary gold(iii ) carbonyl has not been observed before and shows a significant difference in reactivity between (C^C) and (C^N^C)gold(iii ) carbonyls. The latter have been reported to form stable gold(iii ) hydrides via the WGS reaction. In the case of methanol acting as a nucleophile attacking the gold(iii ) carbonyl, no extrusion of CO2 is observed. Instead an intermediary gold(iii ) carboxyl complex forms an aryl carboxylate via reductive C–C bond elimination. Experimental and theoretical studies on the mechanism explain the observed selectivities and give new insights into the reactivity of elusive gold(iii ) carbonyls.